Estabilização e solidificação de Cromo (VI) por biocimentação - Dall'Agnol, Bruna Bilhar (2018)
Most of the soil improvement techniques used in the world involve the addition of mechanical energy and/or synthetic materials, both of which have substantial energy costs associated with their production. However, the technique of biocementation intend to improve the mechanical properties of soil in a sustainable way. Biocementation is the formation of particulate matter through the soil particles through the metabolism of microorganisms present. The numerous microbiological processes have the potential to modify soil behavior. Many bacteria like the species: Bacillus, Sporosarcina, Sporolactobacillus and Clostridium have potential of biological cementation. Thus, the objective of this work was to perform the precipitation of Calcium Carbonate induced by microorganisms or biocementation for the stabilization and solidification of hexavalent chromium (Cr(VI)) in a sandy soil. We perform tests of urease activity, biocementation test, soil and leachate analysis, and SEM. The tests were carried out in the environmental geotechnics laboratory of the University of Passo Fundo. In the first phase of the dissertation, in the test of non-sterilized urease activity, it was possible to observe the adaptation of the native microorganisms of the soil to the nutrient solutions added to the medium. Moreover, in the sterilized urease assay it was possible to observe that the activitymeasured in the absence of microorganisms is considered to be chemical. The zero time in both assays presented similar results, so it was possible to calculate the actual activity performed by microorganisms in the assay. It was also possible to observe that the nutrient solution C stood out with greater activity in the non-autoclaved test. The peak of activity in the time 10 days, being the nutrient solution used in the biocementation test to encapsulate hexavalent chromium in sandy soil, with two feeding intervals, 2 days as used in bibliography and 7 days, approaching the peak of urease found in the first phase of the dissertation. At the end of the second phase, it can be observed from the analysis carried out in the collected leachate that the contaminant retention capacity is higher by the nutrient medium fed specimens, approximately 30%. While the test bodies fed with water showed the lowest contaminant retention, approximately 10%. After that with the results of the soil analysis it was possible to observe that there was biocementation, however, a low concentration was retained in the biocement, thus affirming that in case of field application, the biocementation may not be effective, because in this study approximately 70% of the contaminant inserted in the molding was leached. We concluded with this study that the biocimentation for sandy soils is not efficient with percolation feeding, because the risk of spreading the plume of contamination is high, reducing the efficiency of the technique.